Spotlight on learning styles : teacher strategies for learner success - Rosenburg, Marjorie (Peaslake : Delta Publishing, 2013)
Spotlight on Learning Styles focuses on how we learn rather than what we learn. It sheds light on our individual learning preferences and what we can do to learn and to teach more successfully: - Teachers recognise the characteristics of their own teaching styles.- Learners recognise the characteristics of their own learning styles. The book also provides opportunities for us all to step outside our 'comfort zones' and multiply our possibilities for success.Spotlight on Learning Styles contains three distinctive parts which focus in turn on theory, practice and development:Part A explains the importance and influence of our preferred learning styles, revealing how, as teachers, we can create a more inclusive classroom - integrating and motivating all our students, each with their individual strengths and weaknesses. Part B concentrates on activities we can employ to teach more comprehensively and enable all our students to become successful learners. We discover our own preferred learning styles and those of our students, and activate the Visual, Auditory and Kinaesthetic sensory channels, the Global-Analytic cognitive processes and the Mind Organisation model of perception.Part C introduces further approaches, points to further activities beyond the purely linguistic, and suggests further reading - thus widening the spotlight and providing a springboard for opening up new horizons of discovery and development, of learning and of teaching.
language bookfair2015
Includes bibliographical references (p. 114-115).
Keywords: Learning; Cognitive styles; Englischunterricht